Optimization of Growth and Amylase Production by Aspergillus flavus Grown on Some Agricultural Raw Materials in Nigeria - Oladapo, Oyewale Mojeed (Pakistan Journal of Nutrition, 2013)
Aspergillus flavus exhibited high growth and amylase production. Various Polysaccharides, including soluble starch, sorghum, cassava peel and maize induces high amylase production with maximal amylase activity at 2% W/V. An initial linear increase in amylase activity with increase in substrate concentration was obtained up to 2% W/V. An antagonistic relationship was obtained between amylase activity and substrate concentrations higher than 2% W/V, in the culture filtrate of Aspergillus flavus grown in shake flasks. The maximum growth and amylase production was obtained on the sixth day of incubation at a pH of 7.0 temperature of 29±1°C and 80 rpm. It is concluded from this study that cassava peel as well as sorghum may be an alternative carbon substrate for large scale cultivation of A. flavus for amylase production.